PERMASALAHAN HUKUM YANG BERKAITAN DENGAN UANG PENGGANTI - Triadi, Triadi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The mechanism for implementing criminal compensation for compensation, which is usually more than one month, namely around three months or more, is not in accordance with the provisions of Article 18 paragraph (2) of the Corruption Eradication Law, where the payment period exceeds that which has been determined, namely only one month, and the mechanism for paying criminal compensation money which is done in installments (non-cash) itself does not even have a strong legal basis, even though the purpose of such payments is to make it easier for those convicted of corruption to pay off the replacement money, this convenience does not encourage an increase in the number of convicts who paid the replacement money, but still served the subsidiary sentence, namely prison. Differences in concepts, both in calculating the amount of state losses and in the form of accountability in the form of compensation for state losses caused by criminal acts of corruption, between auditors and prosecutors, result in uncertainty regarding whether or not the accountability of a person convicted of corruption will be complete and the term of the subsidiary crime, as well as the amount of arrears that cannot be reached. guarantee to show that it is the result of a criminal act that has not been accounted for.Keywords: Legal Issues, Replacement Money.